US-guided high-intensity focused ultrasound (HIFU) of abdominal tumors: outcome, early ablation-related laboratory changes and inflammatory reaction. A single-center experience from Germany. (10th September 2021) - Tonguc, Tolga; Strunk, Holger; Gonzalez-Carmona, Maria A.; Recker, Florian; Lütjohann, Dieter; Thudium, Marcus; Conrad, Rupert; Becher, Marc U.; Savchenko, Oleksandr; Davidova, Darya; Luechters, Guido; Mustea, Alexander; et al.
Abstract: Introduction: High-intensity focused ultrasound (HIFU) is an innovative noninvasive procedure for local ablation of different benign and malignant tumors. Preliminary data of animal studies suggest an ablation-associated immune response after HIFU that is induced by cell necrosis and release of intracellular components. The aim of this study is to evaluate if a HIFU-induced early sterile inflammatory reaction is initiated after ablation of uterine fibroids (UF) and pancreatic carcinoma (PaC) which might contribute to the therapeutic effect. Material and methods: A hundred patients with PaC and 30 patients with UF underwent US-guided HIFU treatment. Serum markers of inflammation (leukocytes, CRP, IL-6) and LDH in both collectives as well as tumor markers CA 19-9, CEA and CYFRA in PaC patients were determined in sub-cohorts before and directly after HIFU (0, 2, 5 and 20 h post-ablation) as well as at 3, 6, 9 and 12 months follow-up. Peri-/post interventional imaging included contrast-enhanced MRI of both cohorts and an additional CT scan of PaC patients. Results: An early post-ablation inflammatory response was observed in both groups with a significant increase of leukocytes, CRP and LDH within the first 20 h after HIFU. Interestingly, IL-6 was increased at 20 h after HIFU in PaC patients. A significant reduction of tumor volumes was observed during one year follow-up ( p  < .001) for both tumor entities demonstrating effective treatment outcome. Conclusion: Tumor ablation with HIFU induces an early sterile inflammation that might serve as a precondition for long-term tumor immunity and a sustainable therapeutic effect.